ANALISA PENDAPATAN DAN KELAYAKAN USAHA PEDAGANG DAGING SAPI DI PASAR TRADISIONAL KAMPUNG LALANG KECAMATAN MEDAN SUNGGAL - Rico Farid Alfikri,; Media Agus Kurniawan, (Jurnal Cakrawala Ilmiah, 2024)
Broiler Cattle are livestock that are widely used by the community, one of which is as a producer of animal food in the form of meat and milk, as well as by-products in the form of leather, fertilizer and bones. Beef cattle are one of the providers of meat production as a food source of protein for humans which has high economic value and is important for the community in Medan Sunggal District, Medan City. Selling beef at the Kampung Lalang Traditional market involves traders distributing beef from agents directly to final consumers. This research aims to find out how much income is earned and determine the feasibility of selling beef at the Kampung Lalang Traditional Market, Medan Sunggal District, Medan City from February to completion. Respondents were all beef traders who sold at the Kampung Lalang Traditional Market, Medan Sunggal District, Medan City. The sampling method was carried out by census, the number of respondents was 13 beef traders. The analysis used in the research is Income Analysis and Business Feasibility Analysis. The results of the analysis show that the average amount of profit obtained by traders is IDR. 19,633,077/month. Business feasibility analysis obtained Beef Sales Business Income of 1.10. This means that the business of selling beef at the Kampung Lalang Traditional Market, Medan Sunggal District, Medan City is feasible because R/C > 1